(untitled) (Colombia Medica, 2014)
Background: There is limited information on population-based cancer survival data in Latin America. Objetive: To obtain estimates of survival for some cancers recognized as a public health priority in Colombia using data from the Cancer Registry of Cali for 1995-2004. Methods: All cancer cases for residents of Cali were included for the following sites: breast (3,984), cervix uteri (2,469), prostate (3,999), stomach (3,442) and lung (2,170). Five-year relative survival estimates were calculated using the approach described by Estève. Results: Five-year relative survival was 79% in patients with prostate cancer and 68% and 60% in women with breast or cervix uteri cancer, respectively. The cure fraction was 6% in subjects with lung cancer and 15% in those with stomach cancer. The probability of dying from breast or prostate cancer in people in the lower socio-economic strata (SES) was 1.8 and 2.6 times greater, respectively, when compared to upper SES, p <0.001. Excess mortality associated with cancer was independent of age in prostate or breast cancer. After adjusting for age, sex and SES, the risk of dying from breast, cervix uteri, prostate and lung cancer during the 2000-2004 period decreased 19%, 13%, 48% and 16%, respectively, when compared with the period of 1995-1999. There was no change in the prognosis for patients with stomach cancer. Conclusions: Survival for some kinds of cancer improved through the 1995-2004 period, however health care programs for cancer patients in Cali are inequitable. People from lower SES are the most vulnerable and the least likely to survive.